Comunidades Quilombolas na Amazônia: - Eliane Superti; Gutemberg de Vilhena Silva (Confins)
The aim of this work was to map location, history, life conditions and cultural heritage from quilombola communities in the State of Amapa, considering, for such, the 28 communities certified by Fundação Cultural Palmares (PFC) until January, 2013. The methodological framework used was centered in five fundamental instruments: socioeconomic survey, semi structured interview, anthropological report, photographic register and field notebooks. The questions which guided this production were: Where are they located, what are the origins and life conditions and which cultural heritage content characterizes quilombola communities from Amapa? The article was divided in three parts: Location and History; Life Conditions and, finally, Cultural Heritage. In all of them the discussion about the space given to the culture of the investigated groups pervades presentation and analysis, but each division has a singular objective.